Pengaruh Inovasi Produk dan Kualitas Produk Terhadap Keputusan Pembelian Minuman Isotonik Pocari Sweet di Kabupaten Karawang - Muhamad Fahrul Zalfa Azid; Citra Savitri; Syifa Pramudita Faddila (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Pocari Sweet has been ranked first for a long time as the top brand in the type of isotonic drink. This study is aimed at analyzing the influence of product innovation and product quality on purchasing decisions for the Pocari Sweet isotonic drink in Karawang district. The population in this study were the people of Karawang district who often consumed and knew about various kinds of pocari sweet isotonic drink packaging. The research method is quantitative using purposive sampling with the hair formula which then obtains a sample of 150 respondents. Data analysis uses PLS-SEM to provide predictions and develop theory. The result is that product innovation and product quality have a significant influence on purchasing decisions.